Optimization of the antioxidant capacity, anthocyanins and rehydration in powder of cranberry (Vaccinium corymbosum) microencapsulated with mixtures of hydrocolloids - Arteaga, Ana (2016)
The aim this work was to optimize the antioxidant capacity (CAx), anthocyanins (CA) and rehydration (CR) microencapsulated powder cranberry; based on the mixture of hydrocolloids gum arabic, maltodextrin and modified starch. Cranberry variety Biloxi was used in mature state which the juice is extracted, and solutions were prepared whose composition by weight was 85% juice and 15% of mixtures of gum arabic, maltodextrin and modified starch in different proportions according to the design simplex with extended centroid. Microencapsulation was performed by spray drying at a temperature of 120 °C to obtain microencapsulated cranberry powder, which CAx, CA and CR were determined. ANOVA was performed for regression models being chosen that showed significance (p < 0.05) and good fit (R2aj > 0.7). The model was significant (p < 0.03) and with good fit (R2aj > 0.9) was the special cubico, from which the values that maximize the CAx (52.7% inhibition) and CA (81.56 mg cyanidin 3-glucoside / 100 g) were maltodextrin (11.89%), as amended (12.13%) starch and gum arabic (75.98%). However, the proportions used for CR of microencapsulating had no significant effect.